P533 Correlation of endoscopic and clinical endpoints during induction therapy in patients with moderate-to-severe Crohn's disease: Analysis from CELEST study. (16th January 2018) - Sandborn, W J; Feagan, B; Lewis, J D; Danese, S; Reinisch, W; Rubin, D T; Zhou, W; Cataldi, F; Zhou, Q; Goteti, S; Lacerda, A P
Abstract: Background: The ultimate treatment goal in Crohn's disease (CD) is to achieve remission based on clinical, endoscopic, and biological parameters. Recently, clinical trials evaluating new compounds aim at clinical and endoscopic improvements as co-primary endpoints. The relationships between clinical symptoms and endoscopic disease severity have not been established. This analysis reports correlation of endoscopic remission and response with clinical outcomes in the CELEST study. 1 Methods: A total of 220 adult patients, mean ± SD age of 40.7 ± 12.9 years, CD duration of 13.2 ± 10.0 years, a CD Activity Index (CDAI) 302.8 ± 63.4, average daily liquid/very soft stool frequency (SF) 6.3 ± 3.3, average daily abdominal pain score (AP) 1.8 ± 0.5 and Simplified Endoscopic Score for CD (SES-CD) 15.0 ± 8.4 at baseline (BL), were randomised to double-blind induction therapy with placebo (PBO) or UPA 3, 6, 12, 24 mg twice daily (BID) or 24 mg once daily (QD) for 16 weeks. Follow-up ileocolonoscopy was performed at either Week 12 or 16, per randomised schedule. Correlation of CDAI <150, modified clinical remission, enhanced clinical response (all defined in Table), SF ≤2.8 and AP not worse than BL, and AP ≤1.0 and SF not worse than BL at Week 16 with endoscopic remission and endoscopic response (both defined in Table) at Week 12 of 16 were assessed in all randomised patients who had data at these visits using polychoric correlation. P-values were from Wald test. Results: Correlation coefficients between clinical and endoscopic endpoints are shown in the table. Overall, fair to high statistically significant correlations between endoscopic remission and response at Week 12 of 16 and clinical outcomes at Week 16 were observed. Improvements in the individual CD-symptoms of SF or AP had weaker correlation with endoscopic remission. The strongest correlation was observed between AP ≤1.0 and SF not worse than BL and endoscopic response ( ρ = 0.61). Conclusions: Overall, clinical endpoints in CELEST correlated more strongly with endoscopic response than with endoscopic remission over a 16-week induction treatment period. Clinical remission (based on stool frequency and abdominal pain), and endoscopic response may be the most appropriate co-primary endpoints for short-term induction studies. Reference: 1. Sandborn WJ, et al . 2017;152(Suppl. 1):S1308–9.